Systematic review and meta-analysis of secondary prophylaxis for prevention of HIV-related toxoplasmic encephalitis relapse using trimethoprim-sulfamethoxazole - Connolly, Mark P. (2017)
A recent systematic literature and meta-analysis reported relative efficacy of trimethoprim-sulfamethoxazole (TMP-SMX) for the treatment of toxoplasmic encephalitis (TE) in HIV-infected adults. Here, we estimated relapse rates during secondary prophylaxis with TMP-SMX, and further explored differences in relapse rates prior to introduction of highly active antiretroviral therapy (HAART) and the widespread adoption of HAART. A systematic search of PubMed, Embase, and Cochrane Central Register of Controlled Trials yielded 707 studies whereby 663 were excluded after abstract screening, and 38 were excluded after full review leaving 6 studies for extraction. We performed double data extraction with a third-party adjudicator. Study designs varied with only one randomized study, four prospective cohorts and one retrospective cohort. Relapse rates were transformed using the Freeman-Tukey method and pooled using both fixed-effect and random-effects meta-analysis models. The TMP-SMX relapse rate was 16.4% (95% CI = 6.2% to 30.3%) based on random-effects models. When the disaggregated pre-HAART studies (n = 4) were included, the relapse rate was 14.9% (random effects; 95% CI = 3.7% to 31.9%). Analysis of two post-HAART studies indicated a relapse rate of 19.2% (random effects; 95% CI = 2.8% to 45.6%). Comparing the relapse rates between pre- and post-HAART studies were contrary to what might be expected based on known benefits of HAART therapy in this population. Nevertheless, cautious interpretation is necessary considering the heterogeneity of the included studies and a limited number of subjects receiving TMP-SMX reported in the post-HAART era.